Mediation Effect of Resilience Between Social Support and Depression Symptoms in Patients With Strabismus: A Cross-Sectional Study - Mo Y; Zhang H; Yu X; Xu Z; Xiao H; Gao L; Wang Y (Journal of Multidisciplinary Healthcare)
Yawen Mo,1 Huiting Zhang,1 Xinping Yu,1 Zhihong Xu,1 Huiming Xiao,2 Lingling Gao,3 Yinghuan Wang1 1Department of Strabismus and Amblyopia, State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-Sen University, Guangdong Provincial Key Laboratory of Ophthalmology and Visual Science, Guangdong Provincial Clinical Research Center for Ocular Diseases, Guangzhou, People’s Republic of China; 2Department of Nursing Administration, State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Ophthalmology and Visual Science, Guangdong Provincial Clinical Research Center for Ocular Diseases, Guangzhou, People’s Republic of China; 3School of Nursing, Sun Yat-Sen University, Guangzhou, People’s Republic of ChinaCorrespondence: Lingling Gao; Yinghuan Wang, State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Ophthalmology and Visual Science, Guangdong Provincial Clinical Research Center for Ocular Diseases, No. 54, Xianlie South Road, Yuexiu District, Guangzhou, People’s Republic of China, Email gaoll@mail.sysu.edu.cn; wangyinghuan@gzzoc.comPurpose: The prevalence of depression symptoms in patients with strabismus is high. This study aimed to examine the relationship between social support, resilience, and depression symptoms in patients with strabismus and how the relationship between social support and depression symptoms is mediated by resilience.Patients and Methods: A cross-sectional study was conducted among adult patients undergoing strabismus surgery at an ophthalmic centre in Guangzhou, China, between March 2021 and May 2023. Patients completed the Self-Rating Depression Scale (SDS), Social Support Rating Scale, and Connor-Davidson Resilience Scale. Multiple linear regression and structural equation modeling explored the relationship between social support, resilience, and depression symptoms.Results: Of the 200 patients, 28.5% had depression symptoms (21.5% mild, 6.0% moderate, and 1.0% severe). The mean SDS score (45.50 ± 11.60) was significantly higher than in the healthy reference group (p < 0.001). Social support (β=− 0.407, P< 0.001) and resilience (β=− 0.367, P< 0.001) were predictors of depression symptoms, which explained 44.2% of all variations. Resilience partially mediated between social support and depression symptoms, accounting for 22.22% of the total effect (− 1.543/-6.944).Conclusion: Resilience mediates the relationship between social support and depression symptoms in patients with strabismus. The findings of the present study highlight the importance of social support and psychological resilience in improving depressive symptoms in patients with strabismus.Keywords: strabismus, depression, social support, resilience, mediation effect